2019
DOI: 10.13005/bpj/1620
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents and Hepatoprotective Effect of Suaeda Monoica Forssk and Suaeda Pruinosa Lange

Abstract: The objective of this study is to investigate the chemical constituents of Suaeda monoica and Suaeda pruinosa and evaluate their effects on rat liver intoxicated by over dose of paracetamol. Qualitative analysis of (80%) methanol in water fraction revealed the presence of alkaloids, terpenoids, steroids, tannins, quinones, saponins, flavonoids and phenols from two mangrove species of S. monoica and S. pruinosa was carried out. The compounds were identified from the 80% methanol-H2O fraction as Rutin, quercetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Similar investigations have found that SVE reduces AST and ALT levels elevated by liver damage induced by paracetamol 35 and CCL 4 27 in mouse and rat animal models, respectively. Furthermore, similar hepatoprotective effects have been demonstrated for other Suaeda species, such as S. maritima against concanavalin‐A‐induced hepatotoxicity 50 and S. monoica and S. pruinosa against paracetamol‐induced hepatotoxicity 51 . An earlier study stated that the combination of SVE and doxorubicin showed a synergistic cytotoxic effect against doxorubicin‐resistant HepG‐2 cell carcinoma 27 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Similar investigations have found that SVE reduces AST and ALT levels elevated by liver damage induced by paracetamol 35 and CCL 4 27 in mouse and rat animal models, respectively. Furthermore, similar hepatoprotective effects have been demonstrated for other Suaeda species, such as S. maritima against concanavalin‐A‐induced hepatotoxicity 50 and S. monoica and S. pruinosa against paracetamol‐induced hepatotoxicity 51 . An earlier study stated that the combination of SVE and doxorubicin showed a synergistic cytotoxic effect against doxorubicin‐resistant HepG‐2 cell carcinoma 27 .…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, similar hepatoprotective effects have been demonstrated for other Suaeda species, such as S. maritima against concanavalin-A-induced hepatotoxicity 50 and S. monoica and S. pruinosa against paracetamol-induced hepatotoxicity. 51 An earlier study stated that the combination of SVE and doxorubicin showed a synergistic cytotoxic effect against doxorubicin-resistant HepG-2 cell carcinoma. 27 Herein, we report for the first time a detailed investigation of the in vivo protective effect of SVE against DENA-induced hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…They can be found all over the world on saline and alkaline land, as well as in deserts, lakes, and lakeshores. Suaeda monoica possesses anti-inflammatory, hypolipidemic, cardiotonic, antioxidant, antibacterial, and anti-cancer properties [ 14 ]. Suaeda maritima (L) Dumort, Suaeda monoica Forssk.…”
Section: Introductionmentioning
confidence: 99%